Impacts of Online Retail Business on the Built Environment in the Pandemic Context - Pratama, Giovanny Adi (Smart City, 2021)
The growth of online retail is considerably fast, prompted by the development of information technology and the internet in society. During the pandemic, people are often prohibited by law from commencing activities outside of their homes to prevent virus spreading. This situation made accessing e-commerce for online shopping became a norm. Last year, research presented approximately twenty million visitors increase in Indonesian online retail platforms during the first half of 2020, which was also the earlier phase of the pandemic in Indonesia. The highest-selling products during this period fell in the retail category, including fashion, hobby, and medical drugs and supplies. The two pieces of information indicate that the online retail business was booming because of the pandemic. From architectural perspective, discussions regarding online retail business at its early growth were unfavourable as this business reduces the need for physical commercial buildings or stores. Later, architectural research stated that the business is beneficial as it birthed a new industrial facility known as a fulfilment centre. The booming business and the current favourable impression of online retail became the catalyst of this paper; it provided a short architectural review on the business in the pandemic context and what it may bring for architectural research in the future. This research applies a qualitative approach developed through a structured literature review on the online commercial market during the pandemic, online retail business over time, and related real estate development. The result is a diagram of how the pandemic, technology and the internet, and architecture are correlated and several topic recommendations for future studies.